Synthesis of PDA-Mediated Magnetic Bimetallic Nanozyme and Its Application in Immunochromatographic Assay - Lai, Xiaocui; Zhang, Ganggang; Zeng, Lifeng; Xiao, Xiaoyue; Peng, Juan; Guo, Ping; Zhang, Wei; Lai, Weihua (ACS applied materials & interfaces, 2021)
Immunochromatographic assay (ICA) is widely applied in various fields. However, severe matrix interference and weak signal output present major challenges in achieving accurate and ultrasensitive detection in ICA. Here, a polydopamine (PDA)-mediated magnetic bimetallic nanozyme (Fe O @PDA@Pd/Pt) with peroxidase-like activity was synthesized and used as a probe in ICA. The magnetic property of Fe O @PDA@Pd/Pt enabled effective magnetic enrichment of targets, thereby reducing the matrix interference in the sample. PDA coating on the magnetic bimetallic nanozyme was employed as a mediator and a stabilizer. It improved the catalytic ability and stability of the magnetic bimetallic nanozyme by providing more coordination sites for Pd/Pt growth and functional groups (-NH and -OH). In addition, the Pd/Pt bimetallic synergistic effect could further enhance the catalytic ability of the nanozyme. A method was developed by integrating Fe O , PDA, and Pd/Pt into Fe O @PDA@Pd/Pt as a probe in ICA. With the proposed method, human chorionic gonadotropin and O157:H7 were successfully detected to be as low as 0.0094 mIU/mL in human blood serum and 9 × 10 CFU/mL in the milk sample, respectively. This method may be readily adapted for accurate and ultrasensitive detection of other biomolecules in various fields.